Migration and Hybridity in Kincaid's Lucy, Desai's The Inheritance of Loss and Adichie's Americanah - Yerima, D. (University of Ghana, 2019)
This study investigates in a postcolonial manner, the seeming absence of scholarship of a comparative nature on the link between migration and hybridity on three fronts: the regional front, migrant-status of individuals and gender. It does this using three texts: Lucy by Jamaica Kincaid, The Inheritance of Loss by Kiran Desai and Americanah by Chimamanda Ngozi Adichie which represent the Caribbean, Asian and African regions, respectively. Using the interpretative-historical design, the research explores hybridity’s relationship with migration in the texts to ascertain the relationship between migration and hybridity and, allow for a comparison of the said relationship between them. It also investigates the effects of both phenomena on the characters in different regions based on migrant-status, region and gender difference. Findings from the research reveal that migration and hybridity are caused by lingering effects of colonialism and, globalisation, and are shared experiences of all postcolonial individuals irrespective of region and gender. Secondly, migration is seen to trigger increased expressions of hybridity in characters. While both phenomenaare seen to result in fulfilment with ideological changes, some negative effects like angst, psychosis and discontent are also the plight of characters who engage in migration and/or hybridity.
Seminar
Keywords: Migration; Hybridity; Kincaid's Lucy; Desai's The Inheritance of Loss; Adichie's Americanah